Mapping wheat water use, yield gap and productivity based on climate and satellite data in the Berg River Catchment - Mazango, Joseph Tauyanarwo (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.